EPCO-28. SPHEROID STUDY OF A GLIOBLASTOMA TUMOR IDENTIFIED A SUBCLONAL MUTATION OF EGFR T790M - Rosenberg, Shai (Neuro Oncol, 2020)
BACKGROUND: Glioblastoma (GBM) is the most common and the most devastating primary brain cancer in adults. Precision genetic medicine approach does not provide benefit to majority of GBM patients. A major reason for this is tumor heterogeneity harboring potential resistance mechanisms. Here, we describe an approach to grow spheroids of GBM, containing tumor, stroma and vascular tissues. We show that this approach can identify undetected subclonal driver mutations that can potentially cause drug resistance later in the disease course. METHODS: We grew spheroids of a GBM patient in a multi-well array and monitored them visually. Exome sequencing of the parental tumor (coverage of 557X) and of spheroids after 10 days (n=3) and 20 days (n=5) of growth was performed. In addition, we sequenced six spheroids that were grown for 10 days and treated by Temozolomide for the next 10 days. RESULTS: 70 somatic mutations were detected in the parental tumor. 42/70 of the tumor’s somatic mutations were also detected in the spheroids. 192 somatic mutations were detected in the spheroids only and not in the parental tumor despite high coverage sequencing of the parental tumor. In cancer genes: six somatic mutations were identified in the parental tumor, 5/6 were also detected in the spheroids and 13 mutations were detected only in the spheroids. EGFR V774M mutation was detected in both tumor and spheroids. However – EGFR T790M was independently detected in 7/11 of the spheroids sequenced after 20 days or growth but not in the parental tumor. CONCLUSION: Analysis of GBM spheroids enables detection of rare subclonal mutations not detected in parental tumor. We hypothesize that this is due to positive selection of the ex vivo growth conditions. This analysis enabled detection of EGFR T790M – an important targetable resistance mutation in lung cancer not previously described in primary GBM.